A Huff model with firm heterogeneity and selection. Application to the Italian retail sector. Issue 4 (2nd October 2018) - Del Gatto, Massimo; Mastinu, Carlo S.
ABSTRACT: In this paper, firm heterogeneity (in terms of productivity, i.e., marginal costs) is incorporated into a Huff model of competition in the Italian retail sector. A higher market potential in the trade area is associated with higher average productivity and lower productivity dispersion through selection of the best stores. The analysis, based on a unique data set encompassing 14, 212 Italian retailers, finds support for this relationship in Southern Italy, but not in Northern and Central Italy (where opposite results are obtained in some cases), suggesting the selection dynamics are affected by context factors (other than provincial/regional accessibility) related to an upper geographical scale. The results are robust to controlling for local context factors such as financial risk and floor size restrictions. Floor size restrictions are found to enhance selection.